A regenerator pool dimensioning method to avoid early blocking - Schupke, D.A.; Eder, C.; Blankenhorn, T.; Duhovnikov, S. (HPSR. 2005 Workshop on High Performance Switching and Routing, 2005, 2005)
We propose a method to dimension pools of regenerators which are preconfigured in the network nodes. We aim to minimize the overall number of regenerators in the network, given that a specified number of first connections are not blocked by these regenerators. Furthermore, we propose extensions of the method to minimize the blocking probability after the initial operation phase. The approach uses a connection set-up algorithm as subalgorithm to create a matrix for dimensioning calculation. The effectiveness of the method is assessed for two case study networks.